Comparative Performance Evaluation of CMSIS-RTOS - Renaux, Douglas Paulo Bertrand (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2014: Anais do IV Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2014)
CMSIS-RTOS is an RTOS standard recently defined by ARM to improve portability among micro controller applications. Compliance to this standard can be achieved by design (the case for new RTOSes) or by an adaptation layer on top of an existing RTOS. CMSIS-RTOS has received criticism to its performance, yet, there is no published data comparing its performance to other RTOS. A comparative performance evaluation is conducted against Commercial and FOSS RTOS, resulting in the first published quantitative performance evaluation of CMSIS-RTOS. Contrary to the criticism, the evaluated implementation of CMSIS-RTOS presented no performance penalty when compared to two other classes of RTOS: Commercial and FOSS.